Synthesis, pyrolysis of a novel carborane ceramic precursor, and coating on carbon fiber. (November 2019) - Zong, Yakun; Tong, Dejin; Li, Zhanxiong
A novel carborane–carbosilane–(cyclo-silazane) polymer has been synthesized as precursor of ceramic and applied to the surface treatment of carbon fiber (Cf) by precursor infiltration and pyrolysis method. The preparation of carborane precursor was carried out by hydrosilylation of trivinyltrimethylcyclosilazane with dimethylchlorosilane firstly, and then by polycondensation reaction with hydroxylated 1, 1′-hydroxysilylene-2, 2′-bis(hydroxydimethylsilyl)biscarborane whose −OH was formed by transferring the newly introduced C–H bond via hydroxylation. Chemical structure of the polymer was studied by liquid-nuclear magnetic resonance while evolution of various ceramic phases was studied by Fourier transform infrared spectroscopy and the thermal curing process was studied by thermogravimetric/differential thermal analysis and pyrolysis-gas chromatography/mass spectrometry. The cross-linked polyborosilazane precursor exhibited higher ceramic yield of 65.6% at 1000°C. The coating on the Cf was identified to be uniform, relatively smooth, and continuous with a thickness ranged from 0.1 to 0.5 μm through scanning electron microscope and energy dispersive spectroscopy. Thermogravimetric analysis revealed high temperature stability of the coated Cf in flowing air up to 600°C.